The Antibacterial Activity of Arabian Bidara Leave (Ziziphus spina-christi L.) against the growth of Escherichia coli - Sufiah Asri Mulyawati; Amiruddin Eso; Yusni Nurul Hidayah (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2024)
ABSTRACT Background: The primary cause of mortality for children, according to the World Health Organization, is infectious illnesses. Escherichia coli is one of the bacteria that may infect people. Infections caused by E. coli have historically been treated with antibiotics. Antibiotic resistance, however, can result from improper usage. Arabian Bidara is a plant that has been shown to possess antibacterial qualities, making it a viable alternative therapy. The antibacterial properties of this plant's leaves effectively combat a variety of dangerous germs and pathogens. Purposes: to determine the effectiveness of the ethanolic extract of bidara arabic leaves as an antibacterial against the growth of Escherichia coli bacteria. Methods: This research are an experimental study with a post test only control group design with the independent variable being the treatment of arabic bidara leaf extract, the dependent variable being the zone of inhibition against Escherichia coli . Positive control in the form of ciprofloxacin and negative control using distilled water. The concentrations used were 1500 ppm, 2000 ppm, 2500 ppm and 3000 ppm with three repetitions. Results: This study showed that the ethanolic extract of bidara arabic leaves could inhibit the growth of Escherichia coli bacteria with a strong zone of inhibition at concentrations of 2000 ppm, 2500 ppm, and 3000 ppm and an inhibition zone category classified as weak at a concentration of 1500 ppm. Conclusion: There is antibacterial effectiveness of the ethanolic extract of the leaves of the arabic bidara (Ziziphus spina-christi L.) against the growth of Escherichia coli bacteria. Keywords: Antibacterial; Escherichia coli ; Ziziphus spina-christi L